CSR moderation in the relationship between green investment, CEO gender, environmental cost, and firm value - Febrianto, Hendra Galuh; Priharta, Andry; Hakim, Luqman; Fitriana, Amalia Indah; Ali, Ahmad Fariz bin (Jurnal Akuntansi dan Auditing Indonesia, 2026)
This study examines the impact of green investment, CEO gender leadership, and environmental expenses on business value, with corporate social responsibility (CSR) serving as a moderating factor. A quantitative methodology was used, with panel data from 11 industrial sector firms listed on the Indonesian Stock Exchange between 2020 and 2024. The sample was selected via purposive sampling, and the data were analysed using panel regression in Stata 17. The findings show that green investment, the presence of a CEO gender, and environmental charges all have a significant positive impact on firm value. Furthermore, CSR measured according to the Global Reporting Initiative (GRI) Standards 2021 strengthens the links between green investment and company value, CEO gender leadership and firm value, and environmental costs and firm value. These findings emphasise the strategic importance of CSR in increasing the value relevance of sustainability programs and gender-inclusive leadership. The study contributes to the growing literature on ESG (Environmental, Social, and Governance) by presenting empirical findings from an emerging market environment.